How Volunteers Perceive Psychological Safety at International Events and Its Impact on Their Job Satisfaction - Hui Xu, Guiqiang Qiao (Forest Chemicals Review, 2022)
Volunteershave played an important role in the success of international events. Yet, due to the nature of this short-term informal “job”, volunteers are usually in a disadvantaged situation in this temporary “workplace” and experience a variety of challenges, thus feelings of anxiety or frustration emerged, resulting in dissatisfaction of the “job” and quit from volunteering. However, this is not well addressed in prior research. Psychological safety is proved useful to improve job satisfaction and personnel retention. Adopting a quantitative method, this research is designed to measure volunteers’ perception of psychological safety at international events on the first stage; then, to examine the relationship between psychological safety and volunteering satisfaction with the collected quantitative data (n=489) from two high-impact international events in Hangzhou, China. Regression analysis suggests psychological safety is positively significant associated with volunteers’ job satisfaction. Three factors are found positively significant in predicting their job satisfaction. This research provides new insights into the altruistic volunteerism and volunteer management from the perspective of psychological safety at international events. Thus, it contributes to the literature via applying the theory of psychological safety in event studies area, and provides solutions to improvethe volunteers’job satisfaction through manipulating volunteers’ psychological safety.